2016
DOI: 10.1590/0001-3765201620140595
|View full text |Cite
|
Sign up to set email alerts
|

High temperatures and absence of light affect the hatching of resting eggs of Daphnia in the tropics

Abstract: Temperature and light are acknowledged as important factors for hatching of resting eggs. The knowledge of how they affect hatching rates of this type of egg is important for the comprehension of the consequences of warming waters in recolonization of aquatic ecosystems dependent on dormant populations. This study aimed at comparing the infl uence of different temperature and light conditions on hatching rates of Daphnia ambigua and Daphnia laevis resting eggs from tropical environments. The ephippia were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…Similar inhibition of hatching in darkness was observed in laboratory population of D. pulex by Stross (1966) and in lake-Daphnia by Carvalho and Wolf (1989). Also recent studies on tropical D. ambigua and D. laevis have shown that the absence of light negatively affected hatching of Daphnia dormant eggs (Paes et al, 2016). The existing body of evidence indicates however, that marginal hatching of Daphnia diapausing eggs may occur even without light activation.…”
Section: Discussionsupporting
confidence: 68%
“…Similar inhibition of hatching in darkness was observed in laboratory population of D. pulex by Stross (1966) and in lake-Daphnia by Carvalho and Wolf (1989). Also recent studies on tropical D. ambigua and D. laevis have shown that the absence of light negatively affected hatching of Daphnia dormant eggs (Paes et al, 2016). The existing body of evidence indicates however, that marginal hatching of Daphnia diapausing eggs may occur even without light activation.…”
Section: Discussionsupporting
confidence: 68%
“…However, the authors stated that because they did not separate the eggs contained within the ephippia, this may have adversely affected the results for hatching rates. Paes et al (2016) found that immersion in 2% sodium hypochlorite for 20 minutes did not affect the hatching rates of resting eggs of Daphnia ambigua and did not affect survival as they grow and mature.…”
Section: Discussionmentioning
confidence: 90%
“…A few of the hatching experiments were conducted to test specific extrinsic factors including: predation cues (Santangelo et al, 2010), pH, temperature, light regime Table 1 where the characteristics of each sampled ecosystem are provided. (Rojas et al, 2001;Paes et al, 2016), salinity (Santangelo et al, 2014), drying and temperature pre-treatment of the eggs before hatching tests (Santangelo et al, 2011a), duration of the dry period (Stenert et al, 2009), and the age of the resting stages ( Avila et al, 2015).…”
Section: Reporting Of Methodological Informationmentioning
confidence: 99%
“…a). Similar results were obtained by Paes et al () who showed that high temperatures (from 24 to 32°C) and the absence of light had negative effects on the hatching of Daphnia laevis and D. ambigua in two tropical aquatic environments. On the other hand, conductivity did not appear to affect the hatching response, with values of ca.…”
Section: What Has Been Studied and Howmentioning
confidence: 99%